Analisis Kualitatif Residu Pestisida Pada Bahan Pangan Dengan Menggunakan Metode Kromatografi Lapis Tipis (KLT) - Muawanah Muawanah; Nur Qadri Rasyid (Lontara Journal of Health Science and Technology, 2021)
Vegetables and fruits are foodstuffs whose cultivation process requires pesticides. In addition to farmers who apply pesticides, pesticide poisoning can also be experienced by people who consume agricultural products including vegetables through the pesticide residues contained in them, so that it will have a negative impact on human health who consume them continuously. The purpose of the study was to determine the presence of pesticide residues in foodstuffs. This research is a laboratory observation with a simple random sampling technique. In this study, a qualitative analysis of organophosphate and carbamate pesticide residues in food ingredients was carried out using the Thin Layer Chromatography (TLC) method. Based on the results of the study, from 15 (fifteen) samples of vegetables, no organophosphate chlorpyrifos pesticide content was detected, but the carbamate group was detected in samples of spinach, cabbage, and carrots marked with spots and the Rf value was the same as the Furadan standard. Thus, it is hoped that the community will wash the vegetables before they are processed and consumed.